2020
DOI: 10.1007/978-3-030-38893-5_2
|View full text |Cite
|
Sign up to set email alerts
|

Why Triangular and Trapezoid Membership Functions: A Simple Explanation

Abstract: In principle, in applications of fuzzy techniques, we can have different complex membership functions. In many practical applications, however, it turns out that to get a good quality result-e.g., a good quality control-it is sufficient to consider simple triangular and trapezoid membership functions. There exist explanations for this empirical phenomenon, but the existing explanations are rather mathematically sophisticated and are, thus, not very intuitively clear. In this paper, we provide a simple-and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 8 publications
0
27
0
1
Order By: Relevance
“…The qualitative risk factors in this study were split into three attributes: positive, average, and negative, which served as inputs to the fuzzy logic approach, with bankrupt and non-bankrupt as outputs. The trapezoidal and triangular membership functions were used to define the data's input and output (Kreinovich et al, 2020). The data was graded depending on the membership meaning.…”
Section: Fuzzificationmentioning
confidence: 99%
“…The qualitative risk factors in this study were split into three attributes: positive, average, and negative, which served as inputs to the fuzzy logic approach, with bankrupt and non-bankrupt as outputs. The trapezoidal and triangular membership functions were used to define the data's input and output (Kreinovich et al, 2020). The data was graded depending on the membership meaning.…”
Section: Fuzzificationmentioning
confidence: 99%
“…The theoretical explanation which proves the practicality of trapMFs is discussed in [18]. An intuitive explanation on how trapMF is functioning well is explained in simple terms in [19]. In short, a trapMF ( Figure 1) is defined by a lower limit a, an upper limit d, a lower support limit b, and an upper support limit c, where a < b < c < d [18].…”
Section: Literature Review Trapezoidal Mfmentioning
confidence: 99%
“…In a simple explanation, as an example, for a property such as "small", different values namely x are assigned, along with their degrees, μ(x). The main motivation in fuzzy implementation is to ensure the value x and x' are close, along with their corresponding MFs μ(x) and μ(x') which should be close too [19].…”
Section: Literature Review Trapezoidal Mfmentioning
confidence: 99%
“…In [18][19][20], it is shown that these membership functions are the most robust-in the sense that a given change in the input x to x ≈ x leads to the smallest possible change in the value A(x) of the corresponding membership function; specifically:…”
Section: How This Empirical Fact Is Explained Nowmentioning
confidence: 99%
“…In [20], we describe this requirement in crisp terms-as minimizing the difference between the values of A(x) and A(x ).…”
mentioning
confidence: 99%